2015
DOI: 10.1038/ncomms6957
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable radio-frequency arbitrary waveforms synthesized in a silicon photonic chip

Abstract: Photonic methods of radio-frequency waveform generation and processing can provide performance advantages and flexibility over electronic methods due to the ultrawide bandwidth offered by the optical carriers. However, bulk optics implementations suffer from the lack of integration and slow reconfiguration speed. Here we propose an architecture of integrated photonic radio-frequency generation and processing and implement it on a silicon chip fabricated in a semiconductor manufacturing foundry. Our device can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 59 publications
0
83
0
Order By: Relevance
“…From a broad perspective, a general solution to address the above concerns is a low-loss waveguide technology that enables further device miniaturization through higher index contrast and provides index tuning with high power efficiency and on shorter length scales. In this regard, the siliconon-insulator waveguide technology has shown interesting results [15,16,25,[34][35][36][37], enabling tunable MZ couplers with lengths of tens of micrometers. This offers investigating the realization of the proposed waveguide mesh networks with more than an orderof-magnitude decrease in size (two orders in area).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a broad perspective, a general solution to address the above concerns is a low-loss waveguide technology that enables further device miniaturization through higher index contrast and provides index tuning with high power efficiency and on shorter length scales. In this regard, the siliconon-insulator waveguide technology has shown interesting results [15,16,25,[34][35][36][37], enabling tunable MZ couplers with lengths of tens of micrometers. This offers investigating the realization of the proposed waveguide mesh networks with more than an orderof-magnitude decrease in size (two orders in area).…”
Section: Discussionmentioning
confidence: 99%
“…A more flexible approach would be to design a universal photonic circuit whose topology can be reconfigured, post manufacture, similar to a field-programmable electronic processor, e.g., a field-programmable gate array (FPGA) [30]. This would have variable circuit parameters [9][10][11][12][13][14][15][16][17][18][19][20][21][22] but also a flexible circuit topology to suit a wide range of signal-processing functions. Recently, Pérez et al presented the concept of software-defined processing in microwave photonic systems, addressing the anticipated flexibility requirements in future RF applications [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of designs have been demonstrated to date in these regards. Recently, for example, Wang et al [89] demonstrated an RF arbitrary waveform generator using a silicon circuit with tunable couplers in the order of tens of micrometers; Dai et al [90] demonstrated such couplers with a bandwidth of 140 nm and an excess loss <1 dB; Suzuki et al [91] and Miller [92] showed designs based on lattice cascades of multiple Mach-Zehnder couplers with higher fabrication tolerances. The consideration of all this could be of use for the further development of programmable optical chips which, as one important application, serve as the engine for microwave photonic implementations of reconfigurable RF filters.…”
Section: Various Lattice Mesh Network Designsmentioning
confidence: 99%
“…The use of microwave photonics (MWP) technology in microwave signal generation offers new features and improved performance related to the inherent advantages of operating in the optical domain such as low losses, high bandwidth, immunity to electromagnetic interference (EMI) and, especially in this case, also the possibility of tuning and reconfiguration [3,4].…”
Section: Introductionmentioning
confidence: 99%